2006
DOI: 10.1063/1.2214137
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent properties of solution-grown ZnO nanorods

Abstract: The optical properties of solution-grown ZnO nanorods were investigated using photoluminescence and cathodoluminescence. The as-grown nanorods displayed a broad yellow-orange sub-band-gap luminescence and a small near-band-gap emission peak. The sub-band-gap luminescence can only be observed when exciting above band gap. Scanning cathodoluminescence experiments showed that the width of the sub-band-gap luminescence is not due to an ensemble effect. Upon reduction, the sub-band-gap luminescence disappeared and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 17 publications
4
82
1
5
Order By: Relevance
“…It has been shown that the width of the visible peak, at least for yellow-redshifted peaks, can be directly associated with inhomogeneities within single rods rather than morphology discrepancies among different rods. 19 Comparing the value calculated for the SBE peaks in our case, with values reported in literature for solutiongrown ZnO rods, 19 these relatively narrow ranges seem to indicate that the rods are structurally homogeneous. The attribution of these bands ͑NBE and SBE͒ to the intrinsic defects of the undoped ZnO gives us an interesting insight into the rich defect chemistry of this oxide.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…It has been shown that the width of the visible peak, at least for yellow-redshifted peaks, can be directly associated with inhomogeneities within single rods rather than morphology discrepancies among different rods. 19 Comparing the value calculated for the SBE peaks in our case, with values reported in literature for solutiongrown ZnO rods, 19 these relatively narrow ranges seem to indicate that the rods are structurally homogeneous. The attribution of these bands ͑NBE and SBE͒ to the intrinsic defects of the undoped ZnO gives us an interesting insight into the rich defect chemistry of this oxide.…”
Section: Resultssupporting
confidence: 79%
“…The attribution of the green luminescence ͑GL͒ to the oxygen vacancy is widely accepted, although the contribution of the bulk defects versus the defects on the ZnO surface is still debated. 12,19 We attribute GL to the transition occurring between the energy level occupied by V O 2− and the valence band. As it can be observed from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that room temperature ultraviolet (UV) bandedge photoluminescence with a peak at 374 nm has previously been observed for Sb 2 O 3 nanowires [24]. The purple-blue photoluminescence at 425 nm (~2.92 eV) is probably due to a triplet to ground transition of a neutral oxygen vacancy defect, as suggested by ab initio molecular orbital calculations for many other well-studied metal oxides such as ZnO and SnO 2 [42,43]. Considering that the energy gap of bulk Sb 2 O 3 is 3.3 eV, the purple-blue luminescence from Sb 2 O 3 nanobelts can be attributed to oxygen-related defects that have been introduced during growth.…”
Section: Resultsmentioning
confidence: 77%
“…The sharp peak at 375 nm shows the near-band-edge (NBE) emission. This is generally associated with the excitonic transitions [22], which has been observed between 378-385 nm by earlier workers [23][24][25][26]. A second broad band peak ~485 is noticeable only in nano-ZnS sample and is ascribed to the trap related emission.…”
Section: Resultsmentioning
confidence: 55%